Keragaman Fenotip Sapi Madura dari Perspektif Budaya di Kabupaten Pamekasan: The Diversity of Madura Cattle Phenotypes from A Cultural Perspective in Pamekasan District - Desi Kurniati Agustina; Nurul Hidayati (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2022)
This study aims to characterize the phenotypic diversity of Madura cattle based on their cultural status, namely Sonok and Kerapan Cattle. Phenotypic diversity of madura cattle is used as the basis for the selection of the offspring of madura cattle that show performance to Sonok or Kerapan cattle. This research was conducted at the center of Sonok cattle and Kerapan cattle, namely in Waru and Pademawu districts, Pamekasan Regency. The samples used were 20 Kerapan and 20 Sonok cattle with an age range of 2 - 3 years. The parameters observed included qualitative and quantitative characteristics. The data obtained were analyzed descriptively and made in tabular form for easy discussion. The results showed the quantitative properties of sonok and kerapan cattle respectively, namely for chest circumference 167.50 ± 8.36, 174.15 ± 8.71, body length 127.30 ± 6.37, 160.45 ± 8.02, Tail length 77.95 ± 3.90, 81.10 ± 4.06, horn length 7.00 ± 0.35, 10.55 ± 0.53. Based on the qualitative analysis, Sonok and Kerapan cattle have diversity in terms of coat color, horn shape, eye pattern, eye line, and back line. This diversity can be used as a basis for selection related to its cultural values.